Purification, crystallization and X-ray characterization of a Kunitz-type trypsin inhibitor protein from the seeds of chickpea (Cicer arietinum) - Sharma, Urvashi; Suresh, C. G. (Acta Crystallographica Section F-Structural Biology and Crystallization Communications, 2011)
{A Kunitz-type trypsin inhibitor protein (CPTI) purified from chickpea seeds was estimated to have a molecular mass of 18 kDa on SDS-PAGE. The IC50 value of CPTI was determined to be 2.5 mu g against trypsin. The inhibitory activity of CPTI is 114 TIU (trypsin inhibitory units) per milligram of protein, which is high compared with those of other known Kunitz-type trypsin inhibitors from legumes. CPTI crystallized in three different orthorhombic crystal forms: P2(1)2(1)2 form A, P2(1)2(1)2 form B and P2(1)2(1)2(1). The crystals of P2(1)2(1)2 form angstrom, with unit-cell parameters a = 37.2